Comprehensive Review of Physician Modified Aortic Stent Grafts: Technical and Clinical Outcomes. (April 2021) - Canonge, Jennifer; Jayet, Jérémie; Heim, Frédéric; Chakfé, Nabil; Coggia, Marc; Coscas, Raphaël; Cochennec, Frédéric
Abstract : Objective: Physician modified stent grafts (PMSGs) present satisfactory results in selected cases of complex aortic pathologies. However, the technique lacks standardisation and depends on the surgeon and aortic segment. The aim of this article is to review comprehensively the technical details and clinical results of PMSGs related to patients with pathology in all aortic locations. Methods: A MEDLINE search (last search 20 April 2020) identified 20 relevant papers in the English language published over the last 20 years evaluating clinical outcomes after a PMSG and specifying the technical details to design it. Results: Seven hundred and eleven patients were included in the analyses, with 59% being operated on as an emergency. Ninety-two per cent of abdominal aortic segment PMSGs (A-PMSGs) were performed either as an emergency or before 2012. The main indications were available in 670 cases; 435 were degenerative aneurysms (64.9%) and 171 were aortic dissections (25.5%). Most of the endografts used were composed of polyethylene terephthalate, except for the Ankura (expanded polytetrafluoroethylene [Lifetech Scientific, Shenzhen, China]; n = 50, 7.5%). The Valiant (Medtronic, Minneapolis, MN, USA) represented 65% ( n = 169) of aortic arch PMSGs (aa-PMSGs) and the Zenith platform (Cook Medical, Bloomington, IN, USA) 51% ( n = 139) of A-PMSGs. A snare was used to reinforce the fenestration in 458 PMSGs (66%) and a cautery device cut the fenestration in 484 (75%) PMSGs. No bridging stent was used in 47 (7.0%) PMSGs (these aa-PMSGs had large fenestrations). Technical success ranged from 87.5% to 100% and 30 day mortality from 0% to 8%. Primary branch patency ranged from 96.3% to 100% at 12 month follow up. Zero to 14% of patients experienced type 3 or type 1 endoleak at 14.8 month follow up. Conclusion: PMSG is a useful technique, particularly when validated treatments are not available. However, it is a non-standardised technique and the long term consequences of modifications remain unknown.